Discount Coupons Dematerialization: a Comprehensive Literature Review - Araújo, Jorge (2018)
This article presents a comprehensive literature review regarding digital coupon processing in its various aspects: suppliers, retailers and customers. Current standards, solutions and platforms available in the market and proposed by the scientific community (research, patents, etc.) are presented. A brief summary of the major trends in digital coupon processing is also presented. By resuming the state of the art in digital coupon processing, the article may be useful both for researchers and practitioners interested in the topic.